Do Public-to-Private Leveraged Buyouts Result in Improved Operating Performance? Evidence from the United Kingdom - Asci, Ceylan Cemre (Department of Finance and Tax, 2020)
This study investigates the changes in the operating performance of public-to-private leveraged buyouts (LBOs) backed by one or more private equity firms. For this purpose, this dissertation focuses on a sample of 65 completed public-to-private LBOs in the United Kingdom, which were finalised between 2003 and 2015, and exited by 2018. Specifically, the changes in operating performance in terms of EBITDA/sales, EBIT/sales and EBITDA/total assets, as measured directly and relative to the industry median, before the LBO and at exit by the equity provider, is analysed. A regression methodology from the literature is used to determine the impact of various transaction and company-specific attributes on operating performance changes, based on the shareholder-related agency costs and free cash flow/benefits of debt theories. Surprisingly, the overall picture indicates a negative operating performance change of going-private LBOs in the post-buyout period. The main factors explaining the changes in operating performance seem to be changes in leverage. On the other hand, the hypotheses relating to improved management incentives and improved shareholder monitoring are not supported by the results, as these factors seem to have little to no effect on the operating performance changes related to the public-to-private LBOs in the sample.